Antioxidant, Anti-inflammatory, Antimicrobial and Thrombolytic Activities of Eclipta alba L. Growing in Bangladesh - Barua, Aruna; Kuddus, Md Ruhul; Chowdhury, M Mohi Uddin; Rashid, Mohammad A; Ibrahim, Mohammed (Bangladesh Pharmaceutical Journal, 2023)
Eclipta alba L. (Family: Asteraceae) is an evergreen herb of ethnomedicinal significance in the Indian subcontinent. The present study was carried out to determine the in vitro antioxidant, anti-inflammatory, antimicrobial and thrombolytic activities of n-hexane, chloroform and aqueous soluble fractions of ethanol crude extract of E. alba whole plant. Preliminary phytochemical screening was performed by qualitative tests which revealed the presence of alkaloids, steroids, glycosides, tannins, flavonoids, saponins and amides in E. alba. During the DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging assay, the aqueous soluble fraction of E. alba at a dose of 100 μg/ml showed maximum 87.5% inhibition in scavenging the DPPH radical with IC50 value of 7.86 μg/ml. Anti-inflammatory activity was evaluated by egg albumin denaturation technique and RBC membrane stabilizing method. In both experiments, all the test samples of E. alba showed a concentration-dependent anti-inflammatory potential while the aqueous soluble fraction at the dose of 500 μg/ml demonstrated the maximum 90.12% inhibition of egg albumin denaturation and 78.42% inhibition of RBC membrane hemolysis against hypotonic solution. Antimicrobial sensitivity was evaluated by disc diffusion assay against several bacterial and fungal species. All the test samples at a concentration of 500 μg/disc exhibited noticeable antibacterial (zone of inhibition = 11-23 mm) and antifungal (zone of inhibition = 10-21 mm) activities when compared to the respective standard drug. The aqueous soluble fraction showed maximum activity against Lactobacillus casai (zone of inhibition = 23 mm). During antifungal test, the maximum activity was exhibited by the n-hexane fraction against Pityrosporum ovale (zone of inhibition = 21 mm). During in vitro thrombolytic assay, the aqueous soluble fraction revealed 56.84% lysis of blood clot, as compared to the standard streptokinase (84.60%). The results of our study suggest that E. alba can be considered for further investigation in order to discover the pharmacologically active natural products. Bangladesh Pharmaceutical Journal 26(1): 20-27, 2023 (January)